C55 DAPT IN ELDERLY PATIENTS WITH STEMI OR VERY HIGH RISK NSTEMI: A RETROSPECTIVE STUDY COMPARING TICAGRELOR VS CLOPIDOGREL. (18th May 2022) - Carfora, V; Mazzeo, P; Tarsia, G; Biscione, C; Lopizzo, A; Polosa, D; Grippo, R; Paternò, G; Stabile, E
Abstract: Background: Elderly patients with acute coronary syndrome represent a growing population. The major problem in this population is the balancing of ischemic and bleeding risk. There are poor data from randomized clinical trials on the treatment of acute coronary syndrome in this population. We aim to analyze the best therapeutic strategy in this population. Methods: We performed retrospective study at the Cardiology Department, San Carlo Hospital, Potenza.181 patients with an age ≥ 75 years with STEMI or very high risk NSTEMI were selected from 1 January 2018 to 31 December 2019. Exclusion criteria were anticoagulants therapy, end stage renal disease, cancer in progress and cardiogenic shock at clinical presentation. 43 patients had starter dual antiplatelet therapy with acetylsalicylic acid and clopidogrel and 76 with acetylsalicylic acid and ticagrelor. We aimed to evaluate at 12 months follow up the composite endpoints of ischemic stroke and reinfarction, stroke, bleeding events and death. Results: At the 12–month follow–up, 15 patients died (all–cause mortality of 12.6%). There were 5 strokes (4% of population), 3 in the Clopidogrel group (6.9%) and 2 in the Ticagrelor group (2.6%) without a statistically significant difference (p 0, 7463). The composite endpoint of ischemic events, stroke and reinfarction occurred in 12 patients, 6 in each group, (13.9% in the Clopidogrel group and 7.9% in the Ticagrelor group) but this difference, although indicative, is not statistically significant (p 0.2956). The only statistically significant difference occurred for BARC 2, 3 or 5 bleeding events with a significantly less events in the Clopidogrel group (4.6%) than in Ticagrelor group (18.4%) (p 0, 0345). Conclusion: The elderly patient with STEMI or high–risk NSTEMI represent a group of patients with high ischemic risk but also high bleeding risk. The use of clopidogrel in combination with acetylsalicylic acid should be considered to reduce bleeding events without increasing ischemic events.